Brain-Derived Neurotrophic Factor rs6265 (Val66Met) Polymorphism Is Associated with Disease Severity and Incidence of Cardiovascular Events in a Patient Cohort - Jiang, Rong (Am Heart J, 2017)
BACKGROUND: The rs6265 (Val66Met) single-nucleotide polymorphism in the BDNF gene has been related to a number of endophenotypes that have in turn been shown to confer risk for atherosclerotic cardiovascular disease (CVD). To date, however, very few studies have examined the association of the Val66Met SNP with CVD clinical outcomes. METHODS: In a cohort of 5510 Caucasian patients enrolled in the CATHeterization GENetics (CATHGEN) study at Duke University Hospital between 2001 and 2011, we determined the severity of coronary artery disease (CAD) and CVD event incidence through up to 11.8 years of follow-up. We examined the association of Val66Met genotype with time-to-death or MI, adjusting for age, sex, CAD risk variables, and CAD severity measures. RESULTS: The Val/Val genotype was associated with a higher risk than Met carriers for clinical CVD events (P =0.034, HR = 1.12, 95% CI = [1.01, 1.24]). In addition, compared to Met carriers, individuals with the Val/Val genotype had a greater odds of having more diseased vessels (NDV) (OR = 1.17, 95% CI [1.06, 1.30], P = 0.002), and lower left ventricular ejection fraction (LVEF) (β = −0.72, 95% CI [−1.42, −0.02], P = 0.044). CONCLUSIONS: The Val/Val genotype was associated with greater severity of CAD and incidence of CVD-related clinical events in a patient sample. If these findings are confirmed in further research, intervention studies in clinical groups with the Val/Val genotype could be undertaken to prevent disease and improve prognosis.